PREDICTORS OF FUNCTIONAL IMPROVEMENT IN GERIATRIC REHABILITATION UNITS. A MULTICENTER STUDY - Calle, A. (Innov Aging, 2017)
Frailty-related characteristics, such as sarcopenia, malnutrition and cognitive impairment, are often overlooked, both in practice and research, as potential contributors to functional recovery in patients admitted to geriatrics rehabilitation units. We evaluated the association of these characteristics with functional improvement using data from a multicenter cohort study including patients ≥65 years with orthopedics conditions or stroke from three geriatric rehabilitation units (Barcelona, Spain, and Cremona and Rome, Italy) (December 2014-April 2016). Assessment at admission: demographics, main diagnosis, comorbidity (Charlson Index (CI)), polypharmacy (≥4 drugs), malnutrition (MNA-SF≤11), functional status (Barthel Index), cognitive impairment (MMSE≤23), sarcopenia (EWGSOP definition) and its sub-items (muscle mass through BIA, handgrip strenght and gait speed). Outcome: functional Improvement (FI) (Barthel discharge–admission ≥20, cutoff selected for clinical significance and for identifying upper tertiles Vs lowest). We used logistic regression to test the association between admission variables and FI, introducing sarcopenia and its sub-items in different models. We enrolled 461 patients (mean age±SD=80.6 ± 9.7 years), 34% women, 70% with orthopedic conditions (fractures or prosthesis). Comorbidity (CI=3.76 ± 2.6) and disability (BIa=42.2 ± 21.5) were moderate, sarcopenia was highly prevalent (82%). Better admission Barthel (OR[95%CI]=0.984[0.97–0.99]), admission for stroke (OR[95%CI]=0.357[0.23–0.56]) and cognitive impairment (OR[95%CI]=0.565[0.37–0.87]) independently reduced the likelihood of functional improvement. No other variables were independently associated with the outcome. In conclusion, in our sample, only cognitive impairment, among frailty-related characteristics, is associated to worse functional recovery. A very high prevalence of sarcopenia suggests to better explore this condition and to evaluate possible alternative definitions that better suit rehabilitation settings.